ANALISIS PREFERENSI RISIKO PRODUKSI DAN HUBUNGANNYA DENGAN KEIKUTSERTAAN PETANI DALAM PROGRAM ASURANSI USAHATANI PADI (AUTP) DI KABUPATEN TANJUNG JABUNG TIMUR - Fink Lybaws, Damel; Alamsyah, Zulkifli; Nainggolan, Saidin (JALOW | Journal of Agribusiness and Local Wisdom, 2020)
ABSTRACT Agriculture insurance is offered as one of the funding schemes relating to risk sharing in farming activities. Risk plays as important farmer’s decision to use inputs. This study aimed : (I) to describe the implementation o the AUTP Program in Tanjung Jabung Timur district. (II) Identify production factors influence the risk of rice production, (iii) Farmer’s preferences in acing the risk in rice production, (iv) the relationship of implementing the AUTP Program with behavior of rice farmers. The production function with Just and Pope model was used to knowing influence the risk of rice production, risk preference of khumbakar model was used to estimate risk of rice production. Chi Square test is used to determine the relationship of the implementation of the AUTP Program with behavior of rice farmers. The data obtain from 95 respondents who selected randomly using (simple random sampling). The research result showed that all factors of production effect field rice farming significantly. Meanwhile, partially the use of factors of production seed, NPK fertilizer, urea fertilizer, labour, and land area affect the production significantly on the risk of wetland rice. The average farmer’s preference tend to be risked taker, there is a significant relationship between the farmer participation in the AUTP Program and farmer’s preferences in facing the risk of rice production. Keywords : Risk, Production, Preference, Wetland Rice